The Influence of School Environment on Students' Learning Outcomes in Islamic Religious Education Courses at SMP Muhamadiyah 57 Medan - Febri Nur Indah Hutabarat; Ali Baroroh Al Muflih (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
The school environment is the second main educational environment after the family. Students, teachers administrators, counselors live together and carry out education regularly and well planned. The problem studied in this article is how the environment of SMP Muhammadiyah 57 Medan. How are the students' learning outcomes in Islamic Religious Education subjects at SMP Muhammadiyah 57 Medan. Is there an influence of school environment on student learning outcomes in Islamic Religious Education subjects at Muhammadiyah 57 Junior High School in Medan? Character education involves school culture and family environment, character education is an effort to help develop human potential in order to form morals, character and personality as a whole human being.